OPTIMIZATION OF HYDROCHEMICAL PRECIPITATION PROCESSES FOR THE SELECTIVE RECOVERY OF HIGH-PURITY NICKEL (II) FROM METALLURGICAL TECHNOGENIC SOLUTIONS - Abdullayeva Nigina Abdulhakimovna,Mirzakhmedov Rustamjon Mirxamidovich,Abduqahharova Nilufar Ikrom q (International Journal of Literature and Language Studies, 2026)
This research focuses on the optimization of the hydrochemical precipitation process to selectively recover high-purity nickel (II) from complex multicomponent technogenic solutions generated at the